ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DAN PERUBAHAN ORGANSASI AKIBAT PANDEMI COVID-19 - Maisyura Maisyura; Heriyana Heriyana (Program Studi Administrasi Bisnis, 2021)
Human resources are an absolute strength for the success of an organization, various challenges are faced by the company in achieving its goals, both internally and externally. One of the biggest challenges for companies at this time is the Covid -19 pandemic which has occurred for almost three years, not only in Indonesia. but also in almost all parts of the world. Organizational Citizenship Behavior (OCB) is highly expected in conditions like this, where employees voluntarily show their extra roles outside of the mandatory duties assigned to them, such as helping co -workers without being asked, replacing sick co- workers, giving encouragement, and so on. This paper reviews the dimensions of OCB which consist of altruism, conscientiousness, sportsmanship, courtesy, and civic virtue as well as their role in the company's change management to survive and continue to grow amid the Covid -19 pandemic. Written using a descriptive approach through literacy studies from previous studies, journals and related articles and writings compiled with the author's view, then presented systematically so as to provide an overview of the OCB of company employees in the midst of organizational change due to the Covid-19 pandemic.